Movement Disorders at Onset of Narcolepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2012)
Researchers at University of Bologna; Niguarda Hospital, Milan; and University of Rome, Italy; Montpellier, France; Stanford University, CA, USA; and Institute of Neurology, London, UK analyzed motor features in 39 children with narcolepsy with cataplexy in comparison with 25 age- and sex-matched healthy controls.